Identifikasi Risiko pada Perpustakaan Daerah Gresik dengan NIST SP 800-30 - Dini Idzni Izatri; Nofita Idaroka Rohmah; Renny Sari Dewi (JURIKOM (Jurnal Riset Komputer), 2020)
With the rapid development of technology in Indonesia, several companies and government institutions have begun to implement IT in their systems, as well as the Gresik Regency Regional Library. Information Technology is a field of technology management and covers various fields including but not limited to things such as processes, computer software, information systems, computer hardware, programming languages, and data construction. In short, what makes data, information or knowledge felt in any visual format, through any mechanism of multimedia distribution, is considered part of Information Technology. Regional Library of Gresik Regency is one of the institutions from the government that has implemented Information Technology in their system. Gresik district library has about thirty thousand books consisting of novels, magazines, school textbooks, literature, and others. The Regional Library of Gresik Regency is now using the INLIS LITE application, this application is used by the library, from the collection of books to the list of library members